Perawatan luka pada anjing penderita demodekosis di Klinik Hewan Bogor Pet Center Bogor - Anggraeni, Henny Endah; Komara, Wily Widya; Gulo, Feni Dwi Kartika; Hidayanti, Mustika (ARSHI Veterinary Letters, 2020)
Demodecosis is a skin disease caused by mites Demodex sp. The mites can cause itching and made scratching reflex and made skin damage or wound. Wound is a damage conditions in the skin tissues. Wound care for demodecosis of Pitbull mix dog at Bogor Pet Centre Clinic began with treatment the myiasis and clean the wound 2 times a day and the treatment continues until 19 days topically and orally. Wound healing works well